Influence of structures and lithologies in the morphology and localization of Au–Ag mineralization at Martinetas deposit, Don Nicolas mine, Deseado Massif, Argentina - De Martino, Facundo Julián (2022)
This work describes the structural and lithological controls that affect the distribution, orientation, and precipitation mechanism of mineralization in the Martinetas district, from the structural context and the analysis of the role played by the geological units that host the mineralization. Martinetas is a low sulfidation epithermal gold and silver mining district located in the northeastern sector of the Deseado Massif, Argentina. The district is characterized by numerous quartz veins, sheeted veinlets and breccias, developed in pyroclastic and volcanic rocks of the Bahia Laura Volcanic Complex. The analysis of fractures, faults and host rocks of the vein systems show that the main factors controlling the formation and distribution of the mineralization are the lithology, deformation style and fault kinematics. Their interplay led to positive feedback between the evolution of plane aperture through time, strain localization and the resulting mineralization. Vein orientations are indicative of a NE-SW extensional stress field at the time of hydrothermal fluid ascend, which favored fluid input and pervasive flow within the active fractures and the matrix of the geological units. Subsequently, cyclic channelized fluid flow during repeated fluid input caused extensive veining and numerous filling events. A link between hydrothermal organic matter and the presence of gold in the vein system has been recorded. Knowledge of the structural and lithological controls that set the structure and the distribution of higher grades ore shoots of the mineralization in the Martinetas district constitutes information of high value as an exploratory tool for the region.